Pedagogical content knowledge construction on an STS theme (the union of cultures) by a university teacher, through the application of a Teaching and Learning Sequence - Callejas Restrepo, María Mercedes (2016)
The EANCYT project (translated as: Teaching and Learning Nature of Science and Technology) considers important to train teachers in order to improve their understanding of NoS&T. This paper presents a formative experience, conducted by a university teacher who collaborates with the EANCYT project, through the application of a Teaching-Learning Sequence (TLS): Two cultures or two prejudices?, in the interdisciplinary elective course: “Consolidation of scientific culture”, duringthe 4th semester of a teacher training program, from the University Pedagógica y Tecnológica, in Colombia. For this research process, the researcher conducted all three phases: applied the pre-test, conducted the TLS and applied the post-test. Later on, the researcher reflects upon her teaching action and uses two instruments to collect and present written information related to her Pedagogical Content Knowledge (PCK): Representation of Contents (ReCo) and Code of Professional Experience and Teaching (Rex-PyD). (Loughran, Berry, & Mulhall, 2012; Vazquez and Rodriguez, 2014). Referring to the taxonomy of Science, Technology, Society, Environment topics (Vazquez, 2014), the teaching of two cultures union allows the discussion of the influence of school science onto society, highlighting aspects of integration or separation between the two cultures.